Implementation of Problem Based Learning Model to Measure Communication Skills and Critical Thinking Skills of Junior High School Students - Aziz Rizqi Pratama, Muhammad; Cahyono, Edy; Ulung Aggraito, Yustinus (Postgraduate, Universitas Negeri Semarang, Indonesia, 2019)
Learning also needs to be directed to familiarize students to formulate problems, not only solve problems. In addition, the learning done must train critical thinking skills not just thinking mechanically. The US-based Partnership for 21st Century Skills (P21), identifies the competencies needed in the 21st century namely